Decreasing problematic alcohol use with behavioral strategies: a cognitive model - Darwin, Marielle L., author; Davalos, Deana, advisor; Prince, Mark, committee member; Malcolm, Matthew, committee member (Colorado State University. Libraries, 2020)
Problematic alcohol use is a pattern of hazardous consumption that commonly leads to negative outcomes that affect college students' ability to complete day-to-day responsibilities. Behavioral strategies such as ensuring a safe ride home or avoiding drinking games is linked to a reduction of alcohol-related consequences by providing concrete tactics to enable a change in patterns of consumption. Thus, improving an individual’s ability to utilize these strategies before or during alcohol consumption is targeted in contemporary interventions and preventative approaches. In spite of this practice, much is unknown regarding the underlying cognitive facilities needed to: retain awareness of these strategies, choose approaches in accordance with the situation at hand and update these tactics as needed. If the ability to productively utilize these methods is dependent on cognitive abilities, then individuals with poor cognitive function may be at a disadvantage. The aim of the current study was to investigate the roles of executive cognitive functioning and metacognition as they relate to behavioral strategy usage and adverse alcohol-related outcomes. Results indicate that executive cognitive functioning is inversely related to the number of experienced alcohol-related consequences. Furthermore, low executive function and metacognitive beliefs about alcohol pertaining to the cognitive harm of drinking interacted to significantly affect the use of behavioral strategies, which in turn was inversely related to consequences. The findings of the current study offered a cognitive-based model in support of the practice of employing strategies to decrease alcohol-related consequences, and determined whether implementation of these tactics can successfully take place in those with poor cognitive and metacognitive function.
Keywords: college students; metacognitive beliefs; protective behavioral strategies; executive cognitive function; alcohol-related consequences; problematic alcohol use